On the magnetoionic environments of fast radio bursts. Issue 1 (7th September 2020) - Wang, Wei-Yang; Zhang, Bing; Chen, Xuelei; Xu, Renxin
ABSTRACT: Observations of the Faraday rotation measure, combined with the dispersion measure, can be used to infer the magnetoionic environment of a radio source. We investigate the magnetoionic environments of fast radio bursts (FRBs) by deriving their estimated average magnetic field strengths along the line of sight 〈 B ∥ 〉 in their host galaxies and comparing them with those of Galactic pulsars and magnetars. We find that for those FRBs with RM measurements, the mean 〈 B ∥ 〉 are 1.77^+9.01_-1.48 μ G and 1.74^+14.82_-1.55 μ G using two different methods, which is slightly larger but not inconsistent with the distribution of Galactic pulsars, 1.00^+1.51_-0.60 μ G . Only six Galactic magnetars have estimated 〈 B ∥ 〉. Excluding PSR J1745–2900 that has an anomalously high value due to its proximity with the Galactic Centre, the other five sources have a mean value of 1.70 μ G, which is statistically consistent with the 〈 B ∥ 〉 distributions of both Galactic pulsars and FRBs. There is no apparent trend of evolution of magnetar 〈 B ∥ 〉 as a function of age or surface magnetic field strength. Galactic pulsars and magnetars close to the Galactic Centre have relatively larger 〈 B ∥ 〉 values than other pulsars/magnetars. We discuss the implications of these results for the magnetoionic environments of FRB 121102 within the context of magnetar model and the model invoking a supermassive black hole, and for the origin of FRBs in general.